DFT insights into the sulfidation mechanism of Fe-impurity smithsonite. (15th August 2021) - Luo, Yuanjia; Ou, Leming; Chen, Jianhua; Zhang, Guofan; Jin, Saizhen; Xia, Yuqin; Zhu, Bohan; Zhou, Hanyu
Highlights: The sulfidation of Fe-impurity smithsonite was first studied by DFT. A new insight into effect of impurity on reagents adsorption was proposed. The interaction of H2 O and HS to TZn site on perfect surface was in the order of HS > H2 O. The interaction of H2 O and HS to TFe site on TFe-impurity surface was in the order of H2 O > HS. The hydrophobicity of the formed sulfidation film on the BFe-impurity smithsonite surface greatly decreased. Abstract: The sulfidation-flotation of Fe-bearing smithsonite is still a challenge in practice. Currently, theoretical understandings on reagents adsorption on impurity-bearing mineral surface are still lacking. Here we first systematically investigated the adsorption of HS on perfect and Fe-impurity smithsonite (1 0 1) surfaces in the absence and presence of H2 O by density-functional theory (DFT). We found Fe-impurity dramatically changed the structure and electronic properties of smithsonite surface. In the absence and presence of H2 O, the adsorption energies of HS on Fe-bearing smithsonite surface were all lower than those of perfect surface. The Mulliken bond populations and DOS analysis results showed that the formed Fe-S bonds on Fe-impurity smithsonite surface were less stable than the Zn-S bonds formed on the perfect surface. Meanwhile, the competitive adsorption capacity of H2 O and HS on perfect and Fe-impurity surfaces was different. The interaction of H2 O and HS to TZn site on perfect surface was in the order of HS > H2 O while that to TFe site on TFe-impurity surface was H2 O > HS, and the adsorption of HS was depressed. Furthermore, S-OH was contained in the sulfidation product of BFe-impurity surface, and the hydrophobicity of the formed sulfidation film greatly decreased, which was also not conducive to the sulfidation-flotation.